2010
DOI: 10.1016/j.bbadis.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced creatine kinase as a central and peripheral biomarker in Huntington's disease

Abstract: A major goal of current clinical research in Huntington’s disease (HD) has been to identify preclinical and manifest disease biomarkers, as these may improve both diagnosis and the power for therapeutic trials. Although the underlying biochemical alterations and the mechanisms of neuronal degeneration remain unknown, energy metabolism defects in HD have been chronicled for many years. We report that the brain isoenzyme of creatine kinase (CK-BB), an enzyme important in buffering energy stores, was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 51 publications
1
28
1
Order By: Relevance
“…However, it is unlikely that the decrease of BB-CK that we observed early in the brain of HD mice and that previous studies reported in HTT transgenic mice and HD patients (42,43) is sufficient to produce accumulation of phosphocreatine. When blocking the activity of both cytosolic and mitochondrial CK in skeletal muscle, the levels of phosphocreatine were only minimally affected but phosphocreatine could no longer serve to regenerate hydrolyzed ATP (44).…”
Section: Discussioncontrasting
confidence: 48%
“…However, it is unlikely that the decrease of BB-CK that we observed early in the brain of HD mice and that previous studies reported in HTT transgenic mice and HD patients (42,43) is sufficient to produce accumulation of phosphocreatine. When blocking the activity of both cytosolic and mitochondrial CK in skeletal muscle, the levels of phosphocreatine were only minimally affected but phosphocreatine could no longer serve to regenerate hydrolyzed ATP (44).…”
Section: Discussioncontrasting
confidence: 48%
“…It has been shown that the major ATPbuffering and redistributing system in cells, i.e. the creatine kinase/phosphocreatine system, is severely reduced in human HD [27] . In theory, this should put more demand on the ATP-producing systems, such as glycolysis and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…5 In HD, BCK has also been observed to be reduced, though it is not known whether this is an underlying cause of cell death or a result of disease processes. 6 It is still commonly assumed that the PCr/CK system operates in all cells of the brain. However, there is some evidence that BCK and uMtCK may have quite different cellular distributions.…”
Section: Introductionmentioning
confidence: 99%